No way to escape: a crime fiction - Dzanibe, Nkosivumile (Rhodes University, Faculty of Humanities, School of Languages and Literatures)
This study presents a model for science engagement that incorporates journalistic approaches. This model emerges from a project that aimed to create engagement and communication around a genetically modified sugar cane variety, developed by the South African Sugarcane Research Institute (SASRI). In this project, we engaged with small scale growers in the North and South Coast region of KwaZulu-Natal. This study's methodology is based in action research and an iterative approach to science communication and engagement. It draws and reflects on an action research cycle captured through video documentary as a way to effectively and thoroughly collect, analyse and interpret data and produce through the case study. Based on this action research process a model for science engagement is proposed and reflected on and interrogated by scientists and science communicators through a focus group engagement (see model here as part of this thesis): https://drive.google.com/file/d/14UD1qd4fPcqIZrkESq5v2wgJ1Y2Q7hON/view?usp=sharing. I reflect, using video, on this model and how it incorporates principles and techniques for public engagement drawn from different approaches to journalism and communication studies, I argue that science engagement can benefit from drawing from journalistic approaches to public engagement such as those emerging from development communication, public journalism and development journalism. The submission of this thesis includes various other videos as part of the overall thesis.
Keywords: Creative writing (Higher education) -- South Africa; South African fiction (English) 21st century; Short stories, South African (English) 21st century; Crime fiction; Crime in literature